SrCo0.8Ti0.1Ta0.1O3-δ perovskite: A new highly active and durable cathode material for intermediate-temperature solid oxide fuel cells. (15th May 2021) - Gu, Hongxia; Xu, Meigui; Song, Yufei; Zhou, Chuan; Su, Chao; Wang, Wei; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract: Reducing the operating temperatures of solid oxide fuel cells (SOFCs) to the intermediate-temperature range (IT, 400–650 °C) can bring about several benefits including cost effectiveness, prolonged lifetime and flexible sealing. Nevertheless, the accompanying deterioration of cathodic activity for oxygen reduction reaction (ORR) introduces a large obstacle for commercial applications of IT-SOFCs. Herein, a new perovskite SrCo0.8 Ti0.1 Ta0.1 O3-δ (SCTT) is developed by co-doping titanium and tantalum into the B-site of parent SrCoO3 oxide, which may tackle this problem. At 400–650 °C, SCTT shows high electrical conductivities (65–142 S cm −1 ), appropriate oxygen vacancy concentrations (0.23–0.27) and high bulk diffusion capability due to a synergy between the two dopants in SCTT. Consequently, SCTT exhibits a favorable ORR activity with an area-specific resistance of only 0.17 Ω cm 2 at 500 °C on samaria-doped ceria electrolyte, and the corresponding cell generates a high peak power density (PPD) of 0.90 W cm −2 at 500 °C with negligible performance decay for 180 h. Additionally, SCTT performs well in protonic ceramic fuel cells, achieving a PPD of 0.78 W cm −2 at 650 °C and a high durability for ~176 h at 550 °C. This work provides a new promising cathode material that may accelerate the commercialization of IT-SOFC technology. Graphical abstract: Image 1 Highlights: A new SrCo0.8 Ti0.1 Ta0.1 O3-δ (SCTT) perovskite cathode is developed for SOFCs. SCTT displays superior oxygen reduction activity in both O–SOFCs and PCFCs. SCTT shows well-balanced electrical conductivity and oxygen vacancy concentration. SCTT features large lattice free volume and high bulk diffusion capability. SCTT exhibits excellent operational stability in both O–SOFCs and PCFCs.